First experience of effectiveness and safety of bedaquiline for 18 months within an optimised regimen for XDR-TB. Issue 5 (25th February 2016) - Lewis, Joseph M.; Hine, Paul; Walker, Jenny; Khoo, Saye H.; Taegtmeyer, Miriam; Squire, S. Bertel; Sloan, Derek J.
Extensively drug-resistant (XDR) tuberculosis (TB) is a type of multidrug-resistant (MDR) TB that is resistant to isoniazid, rifampicin, fluoroquinolones and at least one injectable second-line drug. There are insufficient antibiotics for effective combination therapy and mortality exceeds 70% [1]. Following successful phase IIb trials [2] in 2013, the novel mycobacterial ATP-synthase inhibitor bedaquiline was approved in Europe and the USA for the first 24 weeks of MDR/XDR-TB treatment alongside a World Health Organization (WHO)-approved optimised background regimen. Phase III trials are ongoing but cohort data describe good early bacteriological outcomes in France [3, 4], Italy [5], the UK [6], the USA [7], India [8] and South Africa [9]. The first successful use of bedaquiline for 18 months for XDR-TB as part of an optimised background regimen http://ow.ly/XE34x